The Effect of Degree Quality, Career, and Motivation on Students' Interest in Continuing Masters Studies - Amalia, Siti; Afif, M. Nur; Hutomo, Yoyok Priyo (Institut Bisnis dan Informatika Kesatuan, 2024)
The purpose of this study was to determine the effect of quality motivation, career motivation, and degree motivation on the interest of accounting students to continue their master's studies in accounting with tuition fees as a moderating variable. The population in this study was 397 accounting students of the 2020 intake at 5 private universities in Bogor and the sample determination used a simple random sampling technique with the Slovin formula of 80 students. The analytical tools used were multiple linear regression analysis and Moderated Regression Analysis (MRA). The results of the study prove that quality motivation and career motivation partially have a significant effect on the interest in continuing their master's studies in accounting, while degree motivation does not have a significant effect on the interest in continuing their master's studies in accounting. Quality motivation, career motivation, and degree motivation simultaneously have a significant effect on the interest in continuing their master's studies in accounting. Tuition fees as a moderating variable can moderate the effect of career motivation on the interest in continuing their master's studies in accounting, while tuition fees as a moderating variable cannot moderate the effect of quality motivation and degree motivation on the interest in continuing their master's studies in accounting.